2015
DOI: 10.1373/clinchem.2014.236646
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function in Pregnancy: What Is Normal?

Abstract: BACKGROUND:Gestational thyroid dysfunction is common and associated with maternal and child morbidity and mortality. During pregnancy, profound changes in thyroid physiology occur, resulting in different thyroidstimulating hormone (TSH) and free thyroxine (FT 4 ) reference intervals compared to the nonpregnant state. Therefore, international guidelines recommend calculating trimester-and assay-specific reference intervals per center. If these reference intervals are unavailable, TSH reference intervals of 0.1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 83 publications
(109 reference statements)
4
111
2
8
Order By: Relevance
“…Currently, in the absence of a laboratory trimester-specific reference range for TSH, a fixed cutoff of 2.5 mIU/L for the first trimester and 3 mIU/L for the second and third trimester is used (2). However, the reference range for TSH and free T4 can vary with geographic area and race/ethnicity (4,37). Indeed, 12/14 recent studies on reference range found that the upper trimester-specific TSH limit was >2.5 or 3 mIU/L, suggesting that a large number of pregnant women could be overdiagnosed with SCH and subsequently be overtreated when using a fixed TSH cutoff (37).…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in the absence of a laboratory trimester-specific reference range for TSH, a fixed cutoff of 2.5 mIU/L for the first trimester and 3 mIU/L for the second and third trimester is used (2). However, the reference range for TSH and free T4 can vary with geographic area and race/ethnicity (4,37). Indeed, 12/14 recent studies on reference range found that the upper trimester-specific TSH limit was >2.5 or 3 mIU/L, suggesting that a large number of pregnant women could be overdiagnosed with SCH and subsequently be overtreated when using a fixed TSH cutoff (37).…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…However, the reference range for TSH and free T4 can vary with geographic area and race/ethnicity (4,37). Indeed, 12/14 recent studies on reference range found that the upper trimester-specific TSH limit was >2.5 or 3 mIU/L, suggesting that a large number of pregnant women could be overdiagnosed with SCH and subsequently be overtreated when using a fixed TSH cutoff (37). Therefore, adapting a population-based reference range could lead to a more accurate diagnosis of SCH.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…3 Although the foetus can concentrate iodine and synthesise thyroid hormone from [10][11][12] weeks, 4 it is mainly reliant upon the transfer of maternal thyroid hormone until approximately 20 weeks of gestation. 5 As a result most women with hypothyroidism, particularly those with previous surgery or radioactive iodine therapy, will require an increase in thyroxine dose in pregnancy. Many laboratories have developed trimester-specific reference ranges for TSH, but where such reference ranges are not available, the American Thyroid Association and the Endocrine Society recommend an upper limit of 2.5 mU/l in the first trimester, 3 mU/l in the second trimester and 3.5 mU/l in the third trimester.…”
Section: Tsh ≥ 25mu/l In Early Pregnancy; Prevalence and Subsequent mentioning
confidence: 99%
“…Although it has become apparent that this cut-off is too low to define an abnormal TSH (13,14,15,16), the use of this cut-off in the current study leads to a sensible control group of women with a very low risk of having or developing an abnormal thyroid function (e.g. TPOAb-negative women with a TSH of 0.1-2.5 U/L).…”
mentioning
confidence: 93%